Programmed Death Ligand-1 expression in stage II colon cancer - experiences from a nationwide populationbased cohort - Ann C. Eriksen; Flemming B. Sørensen; Jan Lindebjerg; Henrik Hager; René dePont Christensen; Sanne Kjær-Frifeldt; Torben F. Hansen (BMC Cancer, 2019)
Abstract Background Patients suffering from high risk stage II colon cancer (CC) may benefit from adjuvant onco-therapy, but additional prognostic markers are needed for better treatment stratification. We investigated the prognostic value of Programmed Death Ligand-1 (PD-L1) in a true population-based cohort of patients with stage II CC. Methods PD-L1 expression on tumour cells was evaluated by immunohistochemistry in 572 colon cancers. Whole sections from tumour blocks representing the deepest invasive front of the primary tumour were used for analysis. A cut-off of 5% positivity was used for dichotomizing the data. The prognostic value was investigated in Cox proportional hazard models for recurrence-free survival (RFS) and overall survival (OS). Results Overall, 6% of the tumours were classified as high PD-L1. High PD-L1 was related to female gender (p = 0.028), high malignancy grade (< 0.001), right side localization (p < 0.001) and microsatellite instability (MSI) (p < 0.001). Thirty-one (18%) of the MSI and 4 (1%) of the microsatellite stable tumours were classified as high PD-L1, respectively. PD-L1 expression provided no prognostic value as a single marker. In patients with MSI tumours, high PD-L1 expression had no significant impact regarding OS or RFS. Conclusions PD-L1 expression in tumour cells of stage II CC did not provide any prognostic impact, neither in the entire population-based cohort nor in the group of MSI patients. Additional investigations of the immunogenic microenvironment are needed for evaluating the prognostic information in CC.